An algorithm to select a secure twisted elliptic curve in cryptography - Thanh, Dinh Tien; Toan, Nguyen Quoc; Son, Nguyen Van; Duan, Nguyen Van (Journal of Science and Technology on Information security, 2022)
Abstract— Fault attack is a powerful adjacency channel attack technique to break cryptographic schemes. On elliptic curve cryptography (ECC), fault attacks can be divided into three types: safeerror attacks, weak-curve-based attacks, and differential fault attacks. In the paper [1], the author has presented the fault attack on the elliptic curve cryptosystem based on the quadratic twist curve and Proposed criteria to resist elliptic fault attack on the elliptic curve. In this paper, we propose an algorithm to choose a twist secure elliptic curve and evaluate the paths published in cryptographic standards around the world.